Dual Religion in Families A study conducted in Burauen, Leyte and Guiuan, Eastern Samar. - Caspe, Julie Ann B.; Vejera, Kristine Cyrelle Mae A. (Tacloban City Julie Ann B. Caspe and Kristine Cyrelle Mae A. Vajera, 2009)
This study is entitled, Dual Religion in Families: A Study Conducted in Burauen, Leyte and Guiuan Eastern Samar. This aimed to determine how religion affects marriage particularly the conflicts, coping mechanisms and the effect of the differing faiths on children. A total number of 12 families (10-30 years of marriage) with dual religion were interviewed from Burauen, Leyte and Guiuan Estern Samar. The age of the respondents ranges from 30-60 years old. Case study was used in conducting the research and purposive sampling was employed in selecting the respondents. The researchers conducted observation and interview with a paper and pen and a series of guide questions. Recording gadgets was also utilized in conducting the research. The results showed that religion is not really a problem to the family. The respondents revealed that because of different religions, marriage has become a continuous process of adjustment. The usual marital conflicts encountered by the couples were the husbands habitual drinking and financial difficulty. Differences in religious practices were considered a minor conflict or not a conflict at all in the family. An interfaith couple, a Muslim husband and a Roman Catholic wife, who experiences conflict due to religion related how they would sometimes argue about simple things like the food they eat. They also argue about what other people say especially relatives, and activities to which their children should join. Couples resolve conflicts by way of open communication which is the best way to clear out misunderstandings. They also ignore the conflicts and just let the issue pass by although they revealed that it sometimes bother them. The results also revealed that the religion of the child at birth follows the religion of the mother. This shows that the presence of the mother is more influential to the child since mothers are the primary caregivers of the child. The children do not have a problem with regard to the religion of their parents because they were given the freedom to choose their own religion. The couples cope with the demands of their partner's religion by simply ignoring it, respecting and understanding. The results showed that all the respondents of this study were able to preserve their marriage. The factors and ways to lessen conflict may have worked on their present situations. It does not imply that interfaith marriages, in all situations, last long. This study does not intend to overstate the marital success of interfaith couples. Most parents prefer to give their children freedom in choosing their religion. Being born in a home with dual religion may cause confusion to the child. On a positive note, it also gives the child the opportunity to experience God in two distinct ways. As a result, the child, if given the freedom, could choose on fair grounds the religion in which he/she would want to belong.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science